VD_FINDINFO AM 33/20 - 28/2021 vom 30. Juni 2021 - VD Tribunal cantonal (2021)
AM, TRAITEMENT À L'ÉTRANGER, CHANGEMENT DE SEXE, OPÉRATION, DEVOIR DE COLLABORER | 24 LAMal, 25 LAMal, 32 al. 1 LAMal, 34 al. 2 LAMal, 36 OAMal